MANAJEMEN KOMUNIKASI PT. AGAVI DALAM PEMBINAAN KELOMPOK USAHA MIKRO KECIL DAN MENENGAH (STUDY PADA PROGRAM MAHASISWA MAGANG BERSERTIFIKAT DI NUSA PENIDA) - I Kadek Nova Semadi; I Nyoman Yoga Segara; I Wayan Wastawa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
PT. AGAVI is a company that focuses on agriculture and its interaction with society and the environment. Based on the focus of the company's work then gave birth to a certified student internship program. PT. AGAVI is a partner of the Ministry of Education and Culture's MSIB program of the Republic of Indonesia. The aim is to facilitate students in actualizing their skills while helping assisted MSMEs in developing businesses based on existing local potential. The program is made in terms of Collaborative R&D. This research is formulated in 3 problems, namely: relating to communication management patterns, supporting and inhibiting factors of communication management, as well as the implications of communication management at PT. AGAVI in providing guidance to the Young Loka UMKM group through the MSIB program. This type of research is qualitative research. This research is a qualitative research design that focuses on case study observations. This research in determining the informants using purposive sampling technique. Data collection in this study was carried out by observation, interviews, and document collection. Activities carried out by researchers in data analysis are data collection, data reduction, data presentation, and verification. The results of the study show that POAC management in the context of research on apprentice students at PT. AGAVI refers to the management approach used to plan, organize, implement and control various operational and strategic activities related to the production, operation and development of Youth Workshops in Nusa Penida.